The global diffusion of evangelicalism : the age of Billy Graham and John Stott - Stanley, Brian, 1953- (Downers Grove, IL : InterVarsity Press, 2013)
"This volume in the History of Evangelicalism series offers an authoritative survey of worldwide evangelicalism following the Second World War. It discusses the globalization of movements of mission, evangelism, and revival, paying particular attention to the charismatic and neo-Pentecostal movements. Extended treatment is given to the part played by southern hemisphere Christianity in broadening evangelical understandings of mission. The trends in evangelical biblical scholarship, preaching and apologetics were no less significant, including the discipline of hermeneutics in key issues.
While the role of familiar leaders such as Billy Graham, John Stott, Carl Henry, Martyn Lloyd-Jones and Festo Kivengere receives full coverage, space is also given to lesser-known figures, such as Edward Carnell, Agnes Sanford, Orlando Costas, John Gatu and John Laird. The final chapter considers whether evangelical expansion has been at the price of theological coherence and stability, and discusses the phenomenon of "post-evangelicalism." - Back Cover.
Evangelical Christianity in global perspective -- 'Evangelicals', 'conservative evangelicals' and 'fundamentalists' -- Mission, evangelism and revival: the globalization of evangelical networks -- Scholarship, the Bible and preaching -- Defending the faith in a changing cultural climate -- Christian mission and social justice: Lausanne 1974 and the challenge from the majority world -- The ferment of the Spirit: new charismatic and Pentecostal movements -- Hermeneutics, gender and sexual ethics -- Evangelicalism: diffusion or disintegration?
Includes bibliographical references (pages 249-266) and index.
Keywords: Evangelicalism -- History -- 20th century